2022
DOI: 10.3389/fpsyt.2022.1007369
|View full text |Cite
|
Sign up to set email alerts
|

Network connectivity between benevolent childhood experiences and uncertainty stress among Chinese university students

Abstract: BackgroundThe purpose of this study was to explore the association between benevolent childhood experiences (BCEs) and uncertainty stress among Chinese university students by network analysis.MethodsA total of 1,830 university students from three Chinese cities were recruited. Respondents' BCEs and uncertainty stress were self-reported using online questionnaire. The structure of the BCEs-uncertainty stress and related centrality indicators were examined for this sample.ResultsThe overall network model showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…However, higher PCEs predicted higher narcissism (Starbird & Story, 2020) and PCEs were not associated with family-level adaptation to the COVID-19 pandemic . While higher levels of PCEs were associated with lower general perceived stress (Marshall, 2020;Merrick et al, 2019) and lower uncertainty stress (Zhang et al, 2021;Pei et al, 2022), PCEs did not predict parenting stress (Merrick et al, 2019). For parenting outcomes, Abbott (2021) found that higher PCEs predicted more positive self-reported parenting behaviors (i.e., lower psychological and physical aggression, lower neglect towards child), but not parenting attitudes (i.e., spanking and affection beliefs, parenting confidence).…”
Section: Main Effects Of Pces Only (Promotive Effects)mentioning
confidence: 99%
“…However, higher PCEs predicted higher narcissism (Starbird & Story, 2020) and PCEs were not associated with family-level adaptation to the COVID-19 pandemic . While higher levels of PCEs were associated with lower general perceived stress (Marshall, 2020;Merrick et al, 2019) and lower uncertainty stress (Zhang et al, 2021;Pei et al, 2022), PCEs did not predict parenting stress (Merrick et al, 2019). For parenting outcomes, Abbott (2021) found that higher PCEs predicted more positive self-reported parenting behaviors (i.e., lower psychological and physical aggression, lower neglect towards child), but not parenting attitudes (i.e., spanking and affection beliefs, parenting confidence).…”
Section: Main Effects Of Pces Only (Promotive Effects)mentioning
confidence: 99%